Development Model of Senam Ceria Activity Learning for Mental Retardation Students - Arif Adnan Musadi; Wijayanti, Dwi Gansar Santi (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2025)
This study aims to develop a learning model of rhythmic gymnastics activities that are adaptive, interesting, and in accordance with the characteristics of students with disabilities at the Djojonegoro Temanggung State Special School (SLB), Central Java. The model developed is called Cheerful Gymnastics, which is the result of modifying the basic movements of rhythmic gymnastics with a creative and fun approach, accompanied by musical accompaniment that is familiar to children. This study uses the Research and Development (R&D) method referring to the Borg and Gall model, which includes the stages of planning, development, expert validation, small-scale trials, revisions, and large-scale trials. The research subjects amounted to 63 students with disabilities from grades I–VI. The results of expert validation showed a feasibility rate of 88.83% (excellent category). Small-scale trials showed an average result of 78.21% (good category), while large-scale trials showed a significant improvement with an average of 97.44% (very good category). These results prove that Cheerful Gymnastics is effective in improving students' psychomotor, cognitive, and affective abilities, and is suitable for application as a learning model for rhythmic activities in SLB. This model also contributes to the overall increase in motivation, active participation, and physical fitness of students with disabilities